THE ROLE OF TRANSFORMATIVE LEADERSHIP IN MANAGING CONFLICT OVER CHANGES IN ISLAMIC EDUCATION - Muhammad Khoiri; Binti Maunah; Asrop Safi’i (Adisam Publisher, 2025)
This research explores the impact of transformative leadership strategies on improving the performance of Islamic educational institutions. The main focus of the research is how leaders who are able to articulate a clear and inspiring vision and mission can create a more motivated and productive environment. The research results show that there is a strong correlation between the professional development of teachers and staff and improving the quality of learning. Empowering human resources through training and rewards is proven to play an important role in motivating staff to innovate and contribute better. Additional findings highlight the importance of effective communication in the practice of transformative leadership. Leaders who listen to feedback and respond with empathy are able to build strong relationships of trust with staff and students, facilitating better collaboration and creating an environment that values all its members. The leader's ability to manage change and communicate change goals clearly has also proven to be an important factor in the successful implementation of this strategy. The conclusion of this research shows that a transformative leadership approach can bring significant positive changes in Islamic educational institutions. By implementing an inspiring vision, empowering human resources, and effective communication, leaders can create an environment conducive to growth and development, for both students and staff. Therefore, the implementation of transformative leadership strategies should be considered as a potential model for achieving improvements in overall educational performance and quality.